Field Veterinary Survey on Clinical and Economic Impact of Schmallenberg Virus in Belgium. Issue 3 (24th December 2012) - Martinelle, L.; Dal Pozzo, F.; Gauthier, B.; Kirschvink, N.; Saegerman, C.
Summary We implemented a questionnaire‐based methodology targeting veterinary field practitioners to evaluate clinical and economic impact of Schmallenberg virus in Belgium. First suspicious cases were detected as soon as July 2011. The mean cost for individual symptomatic treatment was 65 or 107 Euros, in case of fatal outcome or apparent recovery, respectively.